PENGEMBANGAN PARIWISATA BERBASIS TRI HITA KARANA DI DESA MUNDUK KECAMATAN BANJAR KABUPATEN BULELENG - Adnyana Wayan Arya (Maha Widya Duta : Jurnal Penerangan Agama, Pariwisata Budaya, dan Ilmu Komunikasi, 2018)
Bali tourism began to shift from a tourism pattern based on local wisdom (culture) towards massive and modern tourism. The situation is worsened by the start of the development of many tourist objects presenting western culture and also technological advances. To overcome this, it is necessary to identify the existence of a tourist village which is now being intensified by the government. Previous researches on tourism villages have touched the extent to which the concept of tourism villages is integrated with the value of Tri Hita Karana which has become the spirit of Bali tourism so far. The deepening of this research discussion is expected to provide clarity regarding the development of Tri Hita Karanabased tourism if examined in terms of socioreligious.Keywords: Tourism, Tri Hita Karana, Socio-Religiou